Medição da temperatura de corte no torneamento do aço-ferramenta AISI D6 temperado e revenido auxiliado por LN2 - Lima Júnior, Edmilson Dantas de (2020)
The present work has the main purpose to investigate the cutting temperature when machining quenched and tempered AISI D6 tool-steel assisted by liquid nitrogen (LN2). Uncoated PCBN inserts were used as cutting tools during turning trials. Tool-work thermocouple was the method used in this investigation. In this technique, the contact between the workpiece and the cutting tool makes the hot junction of the thermocouple and the other extremities connected to the workpiece and the cutting tool makes the cold junction. By the Seebeck effect, as long as these junctions are submitted to different temperatures, an electromotive force will arise in the circuit which can be associated with the hot junction temperature. In order to obtain the relation between the hot junction temperature and the generated electromotive force, it was performed a calibration of the system using a conventional lathe. An oxyacetylene flame and an LN2 delivery system were used to obtain high temperatures (from the environment to 800oC, approximately) and low temperatures (including sub-zero temperatures), respectively. In order to minimize undesirable voltage, it was used the concept of physical compensation, where an element made of the same workpiece material was connected to the circuit. The results obtained through the calibration tests show a practically linear behavior between temperature and electromotive force along with the range of temperature used for calibration. Cylindrical turning trials were performed in which the cutting speed and the cooling condition (dry or LN2) were varied. A platform based on Arduino UNO was developed for data acquisition. It was observed a marginal reduction in the cutting temperature in the cryogenic condition compared to the dry condition.